Pengaruh Lokasi Dan Brand Image Terhadap Minat Beli Dan Dampaknya Pada Keputusan Pembelian Pada Café Kopi Dolok Tebing Tinggi - Suwadi, Suwadi; Dewi, Mustika (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This study aims to determine the effect of location and brand image on buying interest and its impact on purchasing decisions Case study at Café Kopi Dolok Tebing Tinggi. The research method used is quantitative method using the help of SPSS version 25.00. which was collected from the results of distributing questionnaires to Café Kopi Dolok consumers as many as 96 respondents. The analysis method used in this study is to use instrument tests, namely validity and reliability tests. Classical assumption test, namely normality test, multicolonearity test, heteroscedacity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the T test and path analysis. The results of SPSS in this study are that the location variable has an effect on purchase interest, the Brand Image variable has no effect on Purchase interest, the location variable has no effect on purchasing decisions, the Brand Image variable has no effect on purchasing decisions, the purchase interest variable has an effect on purchasing decisions, the Purchase Interest variable can mediate the relationship between Location affects purchasing decisions, the Purchase Interest variable can mediate the relationship between Brand Image affects purchasing decisions.